The Impacts of the El Niño and La Niña on Large Grain Producing Countries in ECA : Yield, Poverty and Policy Response - World Bank (World Bank, Washington, DC, 2018)
There is a need to further examine and enhance knowledge concerning the relationship among El Niño and La Niña cycles, drought events, and grain production in the Russian Federation, Ukraine and Kazakhstan (RUK) region, which accounts for more than one third of total wheat exports. This report contributes to close this knowledge gap. A data-driven analysis is utilized to gain a better understanding of (a) the potential impact on grain production of droughts linked to the El Niño/La Niña phenomenon in RUK, (b) RUK governments’ policy response to those events and how domestic and regional grain markets are affected, and (c) the implications for food security and poverty in the RUK region. The results from the analysis suggest that the RUK region’s response to climatic events including droughts must change from reactive to preventive and predictive. It must also consider a broad range of interventions to manage risk. Emerging digital technologies offer unique predictive and diagnostic capabilities that can be coupled with climate-smart agriculture to improve resilience to El Niño and La Niña events